Effects of day time sampling on the activities of termites in oil palm plantation at Malaysia-Indonesia - Saputra A.; Halim M.; Jalaludin N.-A.; Hazmi I.R.; Faszly Rahim (Universiti Kebangsaan Malaysia Press, 2024)
Indexed by Scopus